Association between Parkinson’s disease stages and locomotor performance classification: a pilot study - Vinicius Baia da Silva; Marcelo Coertjens; Lucas Meireles Matos; Leandro Tolfo Franzoni; Leonardo Alexandre Peyré-Tartaruga; Elren Passos-Monteiro (Revista Brasileira de Ciências do Esporte)
ABSTRACT The study aimed to evaluate the impairment of locomotion capacity in people with Parkinson's disease (PwP) using the 6-Minute Walk Test (6MWT), classify performance against predicted distance, and investigate the association between the Locomotion Performance Classification (LPC) (A1, A2, and A3) with the stages between 1 to 4 of the disease, according to the Hoehn & Yahr (H&Y) scale. 32 individuals in stages 1 to 4 of the disease participated. We used Pearson's test in Jamovi software to correlate clinical and performance variables. The performance in the 6MWT was higher than predicted (465m covered; 439m predicted). The stages of the disease and the proposed LPC showed a moderate inverse correlation, r= -0.521; p= 0.002.